Revisiting the Role of Presumptions of Legislative Intent in Statutory Interpretation - Cromwell, The Honourable Thomas A.; Anstis, Siena; Touchie, Thomas (The Canadian Bar Review, 2017)
This paper proposes a fundamental reshaping of the law regarding presumptions of legislative intent in statutory interpretation. Looking to substantive presumptions in particular, it reviews the jurisprudence and concludes that greater consistency would be desirable and that tensions should be resolved between the traditional approach to substantive presumptions and the modern approach to statutory interpretation consistently adopted by the Supreme Court of Canada. Our proposal seeks to provide a uniform methodology for the use of substantive presumptions by incorporating them into the contextual analysis mandated by the modern approach set out in Re Rizzo & Rizzo Shoes Ltd, [1998] 1 SCR 27, 154 DLR (4th) 193. Rejecting the language of “presumptions” and rules of “strict” or “liberal” construction, it argues in favour of interpretation that relies on a transparent discussion of all relevant sources of statutory meaning (including textual and contextual sources, such as the values underlying substantive presumptions) and against a reflexive or mechanical application of substantive presumptions.